Junction tree : the effects of bilingual television programme on vocabulary development of preschoolers in Singapore - Ho, Sheryl Wen Ning (2019)
This study examined the effects of a local preschool bilingual television series, Junction Tree on vocabulary development of a group of preschoolers in Singapore. It aims to investigate if watching Junction Tree would be effective in acquiring new English and Mandarin vocabulary words from the programme with special emphasis on the Mandarin vocabulary acquisition, and its effectiveness in promoting bilingual learning among young children, ages 5 and 6 years old. 11 participants (males = 9, females = 2) from a local preschool were recruited for this study. Using a between-subjects experimental design, 14 episodes from Season 1 of Junction Tree were screened to the viewing group over a period of 3 weeks at the preschool while the control group did not view the programme. The findings showed that children who viewed Junction Tree had a greater increase in programme-specific English production and receptive vocabulary, but no significant effects were found for the Mandarin target words. In addition, vocabulary attributes involving how the words were taught and the frequency of repetition did not influence vocabulary acquisition significantly. Overall, the findings suggest that bilingual television viewing could facilitate vocabulary development of the first language, but more exposure is required for the second language.